The mediation role of the PMO in the transfer of knowledge between projects – a case study of five PMOs. Issue 1 (16th November 2021) - Tshuma, Brighton; Steyn, Herman; van Waveren, Cornelis Cristo
Abstract : Purpose: This article describes advances in the study of knowledge transfer (KT) in project-based organizations (PBOs). Project management offices (PMOs) have both a moderation role and a mediation role to play in KT between projects. In order to improve KT between projects, this paper explores the mediation role of the PMO in the transfer of knowledge with different levels of articulability. The aim is to improve the usability of transferred knowledge. Design/methodology/approach: The case study method was used to investigate KT in five-divisional PMOs within a multinational engineering and project management PBO. Fifteen semi-structured interviews were conducted and the results were analysed using ATLAS.Ti (a computer-aided qualitative data analysis software). Findings: The findings show that it is the way in which the PMO structures knowledge management (KM) infrastructure and processes, which determines the success of its mediation role in the transfer of tacit and explicit knowledge between projects. The articulability of knowledge influences the PMO's mediation role and the PMO's mediation role in turn improves the usability of knowledge, thereby creating a conducive environment for a competitive advantage. Originality/value: This study offers a framework to assist scholars and practitioners to understand the mediation role of the PMO in the transfer of knowledge with different levels of articulability within the projects environment. Such understanding can improve the usability of transferred knowledge, thereby creating a competitive edge for a PBO. The study shows that the PMO can be used as an instrument for KT between projects, a theme that was not found in literature. The paper thus offers new empirical information.